Universality of Dirichlet L-functions with shifted characters - Ramūnas Garunkštis (Lietuvos Matematikos Rinkinys)
We study Dirichlet L-functions with shifted characters L(s, χ, H) = ⅀∞n=1 χ(n+H) ∕ ns, where H is an integer. Here we obtain a joint universality theorem for such functions.